Viabilidade técnica para reuso de efluente em campus universitário - Freire, Bruno da Cunha (Universidade Federal Rural do Semi-Árido, 2019)
Through the current water crisis that plagues the semi-arid region of Brazil, it is necessary to search for forms of water reuse. With this, the objective of this work is to study the technical viability of the reuse of wastewater, aiming at its reuse on a university campus. To do this, it is necessary to characterize the raw and treated effluent, to analyze the facilities and possible barriers to apply effluent reutilization in the campus, to search in the literature Institutions of Higher Education in Brazil that adopt techniques of reuse of residual water and, finely, to propose viable reuse techniques for the campus. The present work can be classified as an exploratory case study in which, at first, the characterization of the study area and the experimental design were done, analyzing each step of the effluent treatment process. Subsequently, the analyzes of the physical-chemical parameters of the effluent were carried out at four different points in the treatment process. The viability of the implementation of a campus-treated effluent reuse system for irrigation activities for landscaping and floor washing purposes is verified as an environmentally correct and economically viable alternative.
Keywords: Recycling of water. Sanitary sewage. University. Compact ETEs. Irrigation.; ENGENHARIAS::ENGENHARIA SANITARIA